IMPACT OF PARENTAL INVOLVEMENT ON SELF ESTEEM, ACHIEVEMENT MOTIVATION AND ACADEMIC ACHEIVEMENT OF IX GRADE STUDENTS - , Amandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Present study is an attempt to find the relationship between parental involvement and achievement motivation of IXth grade students. Parental support has a high impact on their life. They are their life force, they encourage them to achieve high in the their life. Present study was conducted on 200 IXth grade students. The tools used are Parental Involvement scale by Dr. Rita Chopra and Dr. Curable Sahoo, (2006), Self Esteem Inventory by MS Prasad and GP Thakur, (1977) and Achievement Motivation Scale by Pratibha Deo and Asha Mohan, (1985). Statistical technique used were mean, median, t-test and product moment correlation. The results indicates that parental involvement and achievement motivation of IXth grade students are highly correlated and also boys and girls do have different parental involvement. But achievement motivation is same irrespective of gender.